ATAC-king the complexity of SAGA during evolution. - Spedale, G.; Timmers, H.T.M.; Pijnappel, W.W.M.P. (Genes & Development, 2012)
The yeast SAGA (Spt-Ada-Gcn5-acetyltransferase) coactivator complex exerts functions in gene expression, including activator interaction, histone acetylation, histone deubiquitination, mRNA export, chromatin recognition, and regulation of the basal transcription machinery. These diverse functions involve distinct modules within this multiprotein complex. It has now become clear that yeast SAGA has diverged during metazoan evolution into two related complexes, SAGA and ATAC, which exist in two flavors in vertebrates. The compositions of metazoan ATAC and SAGA complexes have been characterized, and functional analyses indicate that these complexes have important but distinct roles in transcription, histone modification, signaling pathways, and cell cycle regulation.